دراسة البنية الإلكترونية للبلورات Cd1-xFexTe بوساطة مطيافية الإصدار الضوئي (Latakia University Journal -Basic Sciences Series, 2018)
تم استخدام مطيافية الإصدار الضوئي بالأشعة فوق البنفسجية عند طاقة hv= 21.22 eV لاختبار البنية الإلكترونية لبلورات Cd1-xFexTe (x=0; 0.04) نصف الناقلة شبه المغناطيسية. أظهرت أطياف الاختبار منحنيات توزيع الطاقة (EDC) للإلكترونات الصادرة من عصابة التكافؤ والإلكترونات الأقرب إلى المستويات اللبية لعصابة التكافؤ Cd4d. تفاعل إلكترونات Fe3d مع إلكترونات التكافؤ أدى إلى ظهور كثافة سويات إضافية في منطقة حرف عصابة التكافؤ في البلورات Cd1-xFexTe عند قمة 0.2eV تحت حرف عصابة التكافؤ. يبين الفرق بين منحنيات توزيع الطاقة (EDC) في عصابة التكافؤ بين البلورتين CdTe    و Cd0.96Fe0.04Te ذروتين لمساهمة الإلكترونات Fe3d6 في عصابة التكافؤ. Ultraviolet Photoemission Spectroscopy (UPS) (hv = 21.22 eV) was used to investigate the electronic structure of Cd1-xFexTe (x=0 and 0.04) semimagnetic semiconductor crystals. UPS spectra showed the energy distribution curves (EDC) of the electrons photo emitted from the valence band and the nearest to the valence band core levels electrons Cd4d of Cd1-xFexTe crystals. Interaction of valence electrons  Fe 3d leads to the appearance of additional density of states in the region of the valence band edge of Cd1-xFexTe crystals. Maximum density was obtained at 0.2eV below the valence band edge. The difference of the valence band EDCs obtained for CdTe and Cd0.96Fe0.04Te presents two peaks of contribution of Fe 3d6 electrons to the valence band.